Evaluation of cowhage (Mucuna pruriens L.) genotypes for growth, yield and quality characters in arecanut plantation under hill zone of Karnataka - Patil, Vinay; Nadukeri, Sadashiv; Kolakar, Shashikala; Bindu, K. Hima (Journal of Plantation Crops, 2019)
Cowhage (Mucuna pruriens L.) is leguminous medicinal plant grown in the tropics. Eight cowhage genotypes were used to study the performance of their growth, yield and quality characters in arecanut plantation under hill zone of Karnataka. Significant differences were recorded in genotypes with respect growth, yield and quality attributes. The genotype Arka Dhanvantari recorded the maximum vine length (282.03 cm) and number of trifoliate leaves (71.03) at harvest. Maximum number of bunches per plant (6.47), stem girth (0.93 cm), pods per bunch (4.00), number of bunches per plant (4.67) and pod yield per plant (136.38 g) was produced in genotype IIHR Selection-2. Genotype Arka Aswini exhibited maximum pod length (11.02 cm) and pod width (1.89 cm) over other genotypes. Maximum seed yield per plant (96.13 g), per plot (2.88 kg) and per hectare (3384.56 kg) was recorded in the genotype IIHR Selection-2. Genotype Arka Aswini exhibited maximum 100 seed weight (136.23 g). Maximum L-DOPA content (5.17 %) was recorded in genotype Arka Aswini which was followed by IIHR Selection-2 (4.69 %). The genotype IIHR Selection-2 recorded maximum L-DOPA yield (4.52 g plant-1).